1990
DOI: 10.1677/jme.0.0050049
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of β-adrenergic agonists on insulin secretion from pancreatic islets isolated from rat and man

Abstract: The selective beta 2-adrenergic agonist clenbuterol was ineffective as a stimulus for insulin secretion when isolated rat pancreatic islets were incubated with glucose at concentrations between 4 and 20 mM. Inclusion of the phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine led to potentiation of glucose-induced insulin secretion, but did not facilitate stimulation by clenbuterol. Furthermore, maintenance of isolated rat islets for up to 3 days in tissue culture also failed to result in the appearance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 0 publications
2
11
0
2
Order By: Relevance
“…Furthermore, there are many studies that support a role for hyperinsulinaemia in the pathogenesis of TPP. First, a nonselective β‐adrenergic blocker, propranolol, which decreases insulin secretion, 10,11 is an effective drug in preventing hypokalaemic paralysis 12 . Second, islet cells require potassium to secrete insulin, thus hypokalaemia during an attack decreases insulin secretion 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are many studies that support a role for hyperinsulinaemia in the pathogenesis of TPP. First, a nonselective β‐adrenergic blocker, propranolol, which decreases insulin secretion, 10,11 is an effective drug in preventing hypokalaemic paralysis 12 . Second, islet cells require potassium to secrete insulin, thus hypokalaemia during an attack decreases insulin secretion 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, mouse and human islets have distinct morphological arrangements, which may impact on their function1011 and several studies comparing the gene expression profiles of human and rodent islets suggest that there are significant differences, including in GPCR expression121314. This has been confirmed functionally in experiments using isolated rodent and human islets where it has been reported that human islets express β-adrenergic receptors that are coupled to elevation of insulin secretion, while β-adrenergic agonists have no effect on insulin release from rat islets15. In addition, MT1 receptors, which are activated by the pineal hormone melatonin, are reported to be expressed by rodent β-cells but not by human β-cells16, and different classes of purinergic receptor regulate intracellular calcium levels in rodent17 and human18 β-cells.…”
mentioning
confidence: 89%
“…Newborn lambs infused with ritodrine hydrochloride demonstrate a progressive rise in insulin/glucose, suggesting direct stimulation of pancreatic β-cell secretion [19]. Human pancreatic β-cells are equipped with both α 2 - and β 2 -adrenoceptors which can affect insulin secretion [20, 21]. Ritodrine is a selective β 2 -adrenoceptor agonist activation of whichstimulates adenylate cyclase with resultantincrease in the intracellular cAMP concentration [22].…”
Section: Discussionmentioning
confidence: 99%